Determination of the utility of groundwater with respect to the geochemical parameters: a case study from Tuticorin District of Tamil Nadu (India) - Singaraja, C.; Chidambaram, S.; Anandhan, P.; Prasanna, Mohan Viswanathan; Thivya, C.; Thilagavathi, R.; Sarathidasan, J. (Springer, 2014)
In modern living, rapid development has created an increase in demand for groundwater. An endeavor has been made to understand the hydrogeochemical parameters to determine the utility of groundwater. This situation is severe in coastal hard rock aquifers due to the influence of salinity ingression and other anthropogenic influence. A total of 135 groundwater samples were collected from the coastal aquifer of the Tuticorin district and analyzed for major cations and anions during premonsoon (PRM) and postmonsoon (POM). The ions analyzed were used to determine the drinking, agricultural and domestic utility of groundwater. The electrical conductivity (EC) contour shows that the groundwater quality is poor along the coast. The parameters were compared with WHO (Guidelines for drinking water quality recommendations, WHO, Geneva, 2004) standard for drinking purpose. A groundwater classification method has been developed for groundwater in the area using a dynamic water quality index (WQI). On the basis of the WQI so computed, groundwater in the area has been spatially classified into “excellent,” “good,” “poor” and “very poor” to “Unsuitable” water types variation lithologywise. Corrosivity ratio and hardness were noted to be higher and found to be unsuitable in majority of the regions for domestic purpose. Higher fluoride concentration was noted in the central part of the study area represented by complex geology comprising of the hornblende biotite gneiss and charnockite. Sodium percentage (Na%), sodium absorption ratio, residual sodium carbonate, Wilcox (Classification and use of irrigation waters, US Department of Agriculture, Washington, 1955), permeability index, residual sodium bicarbonate, magnesium hazard, Kelly’s ratio and potential salinity also indicate that most of the groundwater samples are not suitable for irrigation purposes.